Medial wall fragment involving large posterior cortex in pertrochanteric femur fractures: a notable preoperative risk factor for implant failure. Issue 3 (March 2020) - Li, Pengfei; Lv, Yang; Zhou, Fang; Tian, Yun; Ji, Hongquan; Zhang, Zhishan; Guo, Yan; Yang, Zhongwei; Hou, Guojin
Highlights: A classification was introduced for medial wall fragment in pertrochanteric femur fractures based on 324 cases; Type III fractures had a significantly increased failure rate and reduction of the medial wall fragment and fixation should be considered during surgery using intramedullary nails.; Abstract: Introduction: To introduce a classification for medial wall fragments in pertrochanteric femur fractures and investigate potential preoperative predictors of implant failure following fixation. Material and methods: Medical records of 324 adult patients receiving routine operative treatment using intramedullary devices for pertrochanteric femur fractures with medial wall fragments between August 2008 and May 2018 were retrospectively analyzed. Potential predictors including age, gender, body mass index, comorbidities, AO/OTA classification of fractures were noted. The medial wall fractures were categorized into three types: 1) Type I: avulsion of the lesser trochanter; fracture line does not exceed the base of the lesser trochanter; 2) Type II: fragment involving the posterior cortex near the base of the lesser trochanter; fracture line does not reach the midline of the posterior wall; 3) Type III: fragment involving the large posterior cortex; fracture line reaches or exceeds the midline of the posterior wall. Results: The 8 (2.5%) implant failures comprised 1 in 186 Type I fractures, 1 in 76 Type II fractures and 6 in 62 Type III fractures. The failure rates of each fracture type were 0.5% in Type I, 1.3% in Type II and significantly increased to 9.7% in Type III (odds ratio [OR], 19.821; 95% confidence interval [CI], 2.337-168.135; p=0.001). Conclusions: Type III fractures had a significantly increased failure rate. It is important for orthopedists to identify Type III fractures presurgically, reduction of the medial wall fragment and fixation should be considered during surgery using intramedullary nails.